On the problem of vibration protection of rotor systems with elastic adaptive elements of quasi-zero stiffness - Klitnoi, Volodymyr; Gaydamaka, Anatoliy (Polskie Towarzystwo Diagnostyki Technicznej, 2020)
The analysis of scientific publications for rotor systems on the elastic supports made it possible to develop a basic version of the design scheme of active elastic support with controlled quasi-zero stiffness based on adaptive piezoceramic elements. The main components of the mathematical model of the functioning of active elastic supports with controlled quasi-zero stiffness based on adaptive piezoceramic elements are substantiated, which will help create the foundations of a theory for solving the problem of effective vibration protection. Numerical results show the possibility of effective applying of the proposed solution to the problem of rotor vibration damping.
Keywords: rotor systems; supports with quasi-zero stiffnes; adaptive materials; piezoceramics